Institutional Crisis in 21st-Century Britain - Richards, David; Smith, Martin; Hay, Colin; SpringerLink (Online service) (London : Palgrave Macmillan UK, 2014)
In 21st century Britain, a'perfect storm' seems to have engulfed many of its institutions. This book is the first wholesale consideration of the crisis of legitimacy that has taken root in Britain's key institutions and explores the crisis across them to determine if a set of shared underlying pathologies exist to create this collective crisis.
Keywords: Political science; Political theory; Democracy; Public policy; Elections; Great Britain -- Politics and government; Political sociology; Political Science and International Relations; Public Policy; Democracy; Electoral Politics; British Politics; Political Sociology; Political Theory